2016
DOI: 10.1103/physrevd.93.082002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the kinematic Sunyaev-Zel’dovich effect with the Atacama Cosmology Telescope and velocity reconstruction from the Baryon Oscillation Spectroscopic Survey

Abstract: We use microwave temperature maps from two seasons of data from the Atacama Cosmology Telescope (ACTPol) at 146 GHz, together with the 'Constant Mass' CMASS galaxy sample from the Baryon Oscillation Spectroscopic Survey to measure the kinematic Sunyaev-Zel'dovich (kSZ) effect over the redshift range z = 0.4 − 0.7. We use galaxy positions and the continuity equation to obtain a reconstruction of the line-of-sight velocity field. We stack the cosmic microwave background temperature at the location of each halo, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 59 publications
2
128
0
Order By: Relevance
“…This enables us to compare the temporally varying state variables of the medium as well as the time-integrated quantities with those of existing models and observations and test the validity of the model which grows halos smoothly over cosmological times. The thermodynamics of the gas in clusters and groups is interesting to study, particularly with the advent of future galaxy redshift surveys and the measurement of the kinetic and thermal Sunyaev-Zel'dovich signal (Lim et al 2017, Park, Alvarez & Bond 2018, Schaan et al 2016) combined with the existing X-ray observations. In order to test a large number of ICM models and reasonable parametric profiles to compare with new observations, simple semi-analytical models (Flender, Nagai & McDonald 2017 ) are preferred over large scale hydrodynamic simulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This enables us to compare the temporally varying state variables of the medium as well as the time-integrated quantities with those of existing models and observations and test the validity of the model which grows halos smoothly over cosmological times. The thermodynamics of the gas in clusters and groups is interesting to study, particularly with the advent of future galaxy redshift surveys and the measurement of the kinetic and thermal Sunyaev-Zel'dovich signal (Lim et al 2017, Park, Alvarez & Bond 2018, Schaan et al 2016) combined with the existing X-ray observations. In order to test a large number of ICM models and reasonable parametric profiles to compare with new observations, simple semi-analytical models (Flender, Nagai & McDonald 2017 ) are preferred over large scale hydrodynamic simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Galaxy clusters, on the other hand, have been observed to contain the highest baryon content (Ettori 2003). Schaan et al 2016 discuss the baryon content of clusters and groups by combining data from Atacama Cosmology Telescope and "Constant Mass" CMASS galaxy sample from the Baryon Oscillation Spectroscopic survey to measure the kinetic SZ signal of the halos over the redshift range 0.4 − 0.7. They consider the kSZ signal obtained relative to the expected kSZ signal to be a proxy for the average baryon content.…”
Section: Baryon Fraction Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of kSZE has so far been made only for a small number of systems (e.g Kashlinsky et al 2010) and from statistical measurements based on, e.g., the pair-wise and cross correlation methods (Hand et al 2012 Schaan et al (2016) found that a significant fraction of baryons may be associated with the large-scale structure traced by galaxies. A similar conclusion was reached by Hill et al (2016) by cross-correlating galaxies with CMB maps.…”
Section: Introductionmentioning
confidence: 99%
“…We set σ to be the angular projection of the halo virial radius θ 200c . DGD3 can be thought of as a dipolar generalization of the aperture photometry filter used for kSZ detection (Li et al 2018;Soergel et al 2016;De Bernardis et al 2017;Schaan et al 2016). Evaluating Eq.…”
Section: Differential Gaussian Derivative Filtermentioning
confidence: 99%